The Measure of Success: A Mentoring Project - Campbell, Valerie (Operating Room Nurses Association of Canada Journal, 2000)
Lions Gate Hospital in North Vancouver, British Columbia is a 323-bed acute and long term care community hospital and a part of the North Shore Health Region (NSHR). It supports a busy eight-theatre operating room, which covers all specialties except open heart. Along with many other hospitals in the country, we currently find ourselves critically short of experienced operating room nurses. Of course the operating room is not the only area to be affected by nursing shortages.